PENGARUH HASIL BELAJAR MATERI ADAB BERPAKAIAN PADA MATA PELAJARAN AQIDAH AKHLAK TERHADAP ETIKA BERBUSANA DI LUAR SEKOLAH SANTRIWATI KELAS XI MA PONPES NURUL ISLAM KAMPUNG BARU KECAMATAN GUNUNG TOAR - Pebrianti Putri; Ikrima Mailani; A. Mualif (Universitas Islam Kuantan Singingi, 2023)
This research is motivated by the development of the times, clothing models have develoved very rapidly and have given rise to many new ideas in designing creative clothing. But there are still many clothing models that have not been Syar’i criteria in making and designing the clothes. Even though we know that the model of clothing that display body curves is not something that is commaded and taught by allah and his. Messanger based on the background and phenomena above, research this study aims to find out wheter the is any effect of learning outcomes on dressing etiquette on moral aqidah subjects on dress ethics outside the shcool of class XI MA Islamic boarding shcool nurul islam kampung baru, gunung toar district. This researt is a quantitative explanation level, which n at MA islamic boarding school nurul islam kampung baru kecamatan gunung toar district. The data collaction technique used was a questionnaire with instruments in the form of questiunnaires, interviews and dokumentation. Data analysis used a simple linear regression formula which was processed using the SPSS soffware. The equation that the value (sig) is 0. 186 probability D. 0, 05 so it can be concluded that there is no effect of the X variable on Y.